Case Report: Perioperative Kounis Syndrome in an Adolescent With Congenital Glaucoma - Capponi, Guglielmo; Giovannini, Mattia; Koniari, Ioanna; Mori, Francesca; Rubino, Chiara; Spaziani, Gaia; Calabri, Giovanni Battista; Favilli, Silvia; Novembre, Elio; Indolfi, Giuseppe; De Simone, Luciano; Trapani, Sandra (Frontiers in Cardiovascular Medicine, 2021)
A 12-year-old male patient suffering from congenital glaucoma developed bradycardia, myocardial injury, left ventricular failure and hypotension after induction of anesthesia. Electrocardiography and echocardiography revealed a complete normalization of ECG and a complete spontaneous recovery in the cardiac function 72 hours from the beginning of the clinical manifestations, while cardiac Magnetic Resonance Imaging and coronary Computed Tomography scan revealed a myocardial bridge of a tract of the left anterior descendent coronary artery. Diagnosis of Kounis syndrome was made, a relatively novel, under-recognized clinical condition, defined as the manifestation of an acute coronary syndrome accompanied by mast cell activation and platelet aggregation involving interrelated and interacting inflammatory cells in the setting of allergic, hypersensitivity, anaphylactic or anaphylactoid insults. In children, this syndrome has been only described in isolated case reports or small case series. Thus, it appears critical to report new cases of KS in children to increase the awareness of this disease in pediatric healthcare workers so as to enhance its early recognition and optimal therapeutic strategy. Furthermore, it appears of paramount importance the implementation of universal guidelines accepted by allergology and cardiology societies, in order to standardize the management of pediatric and adult patients with KS.